Analysis The Role OF BUMDES In Management On Sambibulu Agrotourism - Almalia Oktadianti; Hendra Sukmana (Universitas Muhammadiyah Sidoarjo, 2022)
This writing aims to analyze and constrain the role of BUMDes in the Management of Sambibulu Agrotourism, Taman District, Sidoarjo Regency. The problem with the BUMDes of Sambibulu Agrotourism village tourism is that human resources have not been fully met in the management of the Sambibulu Agrotourism BUMDes. This writing method uses descriptive qualitative, data collection techniques are carried out by in-depth interviews, observations and reviewing the relevant literature. The technique of determining the informants in this study used purposive sampling. The informants in this writing are the Chairperson of the Sambibulu BUMDes Management, the Sambibulu BUMDes Treasurer, the Youth Organization Members, and the Sambibulu BUMDes Management Members. The analysis technique in this paper is a type of qualitative analysis referring to the theory of Miles and Huberman. The results of the study show that with the role of BUMDes in the management of village tourism, it is hoped that the community can participate in managing the location of Agrotourism. The obstacle in the process of the role of BUMDes is the lack of public awareness to think critically in processing BUMDes, so the mindset of the community needs intense handling from the environment that supports the existence of this Tourism BUMDes. Related to the mindset of the community that is lacking in organization, the local government and related agencies must provide regular counseling to the village community.